Conversion From Continuous Infusion Fentanyl to Continuous Infusion Hydromorphone in the Pediatric Intensive Care Unit. Issue 12 (December 2021) - Harkin, Maura; Miller, Jamie L.; Lim, Sin Yin; Neely, Stephen B.; Walsh, Christina K.; Johnson, Peter N.
Background: Opioid rotations from fentanyl to hydromorphone may reduce opioid/sedative exposure in critically ill children. Objective: The primary objective was to determine the conversion percentage from fentanyl to hydromorphone infusions using equianalgesic conversions (0.1 mg fentanyl = 1.5 mg hydromorphone). Secondary objectives included identification of the median time and hydromorphone rate at stabilization (defined as the first 24-hour period no hydromorphone rates changed, 80% of State Behavioral Scale [SBS] scores between 0 and −1, and <3 hydromorphone boluses administered). Additional outcomes included a comparison of opioid/sedative requirements on the day of conversion versus the three 24-hour periods prior to conversion. Methods: This retrospective study included children <18 years old converted from fentanyl to hydromorphone infusions over 6.3 years. Linear mixed models were used to determine if the mean cumulative opioid/sedative dosing differed from the day of conversion versus three 24-hour periods prior to conversion. Results: A total of 36 children were converted to hydromorphone. The median conversion percentage of hydromorphone was 86% of their fentanyl dose (interquartile range [IQR] = 67-100). The median hydromorphone rate at stabilization was 0.08 mg/kg/h (IQR = 0.05-0.1). Eight (22%) were stabilized on their initial hydromorphone rate; 8 (22%) never achieved stabilization. Patients had a significant decrease in opioid dosing on the day of conversion versus the 24-hour period prior to conversion but no changes in sedative dosing following conversion. Conclusion and Relevance: A median 14% fentanyl dose reduction was noted when transitioning to hydromorphone. Further exploration is needed to determine if opioid rotations with hydromorphone can reduce opioid/sedative exposure.